The mitigating effect of dietary β-glucan against fipronil-induced intoxication in Nile Tilapia (Oreochromis niloticus): Histopathological, immunological, hematological, and biochemical analysis - Fawiziah Khalaf Alharbi (Open Veterinary Journal)
Background: Due to its remarkable effectiveness against a wide range of pests and insects at very low concentrations, the broad-spectrum fipronil pesticide is currently gaining popularity in the agricultural, public health, and international industries. However, the stressor effects of fipronil insecticides cause ecological disruption, growth retardation, immunosuppression, and higher fish mortality rates. Both animals and humans have demonstrated the effectiveness of prebiotics such as β-1,3-glucan in their diets. Aquaculture has recently increased in use because of its potential to control diseases, compete with environmental stresses, and promote fish growth.